INDENTIFIKASI TELUR CACING SOIL TRANSMITTED HELMINTHES (STH) PADA SAYURAN SELADA (LACTUCA SATIVA) DAN SAYURAN KUBIS ((BRASSICA OLERACEA) YANG DIJUAL DI PASAR TRADISIONAL DI KECAMATAN MEDAN AREA - MELVIA RIFDHA; IQRINA WIDYA ZAHARA (LP2MTBM MAKARIOZ, 2023)
Soil Transmitted Helminths (STH) infection is endemic that still often occurs in many areas of the world, especially in developing countries with poor environmental sanitation and personal hygiene. To identify the presence of Soil Transmitted Helminths eggs in lettuce (Lactuca sativa) and cabbage (Brassica oleracea) which are sold in traditional markets in Medan Area. This type of research uses descriptive analytical research method with observations made only once and for a certain time. This research uses a cross sectional approach. The results of positive contamination on lettuce (Lactucasativa) worms that mostly affected were Ascaris lumbricoides worms as much as 16.7%, Trichuris trichiura as many as 8.3%, and Necator americanus as much as 8.3%. The most common worm contamination in cabbage (Brassica oleracea) is Ascaris lumbricoides worm as much as 14.8%, Trichuris trichiura as much as 3.7%, and Necator americanus as much as 3.7%. The results of this study were the most STH contamination in lettuce (Lactuca sativa)